2022
DOI: 10.3390/molecules27206863
|View full text |Cite
|
Sign up to set email alerts
|

A Unique, Porous C3N4 Nanotube for Electrochemiluminescence with High Emission Intensity and Long-Term Stability: The Role of Calcination Atmosphere

Abstract: Developing excellent strategies to optimize the electrochemiluminescence (ECL) performance of C3N4 materials remains a challenge due to the electrode passivation, causing weak and unstable light emission. A strategy of controlling the calcination atmosphere was proposed to improve the ECL performance of C3N4 nanotubes. Interestingly, we found that calcination atmosphere played a key role in specific surface area, pore-size and crystallinity of C3N4 nanotubes. The C3N4 nanotubes prepared in the Air atmosphere (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…[14][15][16] Previous studies have shown that calcination in different atmospheres often leads to changes in the structure and properties of metal oxide nanomaterials. [17][18][19] This difference often leads to completely different application values of these nanomaterials in electrochemistry, 20,21 environmental protection, 22,23 catalytic activity, 24,25 etc. However, few people investigated the performance differences of transition metal oxide nanomaterials formed in different calcination atmospheres for biotherapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Previous studies have shown that calcination in different atmospheres often leads to changes in the structure and properties of metal oxide nanomaterials. [17][18][19] This difference often leads to completely different application values of these nanomaterials in electrochemistry, 20,21 environmental protection, 22,23 catalytic activity, 24,25 etc. However, few people investigated the performance differences of transition metal oxide nanomaterials formed in different calcination atmospheres for biotherapeutic applications.…”
Section: Introductionmentioning
confidence: 99%